Impact of age on the efficacy of oxaliplatin in the preoperative chemoradiotherapy and adjuvant chemotherapy of rectal cancer: a post hoc analysis of the CAO/ARO/AIO-04 phase III trial. (4th June 2018) - Hofheinz, R -D; Arnold, D; Fokas, E; Kaufmann, M; Hothorn, T; Folprecht, G; Fietkau, R; Hohenberger, W; Ghadimi, M; Liersch, T; Grabenbauer, G G; Sauer, R; et al.
Abstract: Background: The German rectal cancer trial CAO/ARO/AIO-04 has shown a significant benefit in 3-year disease-free survival (DFS) of adding oxaliplatin to a standard preoperative 5-fluorouracil (5-FU)-based chemoradiotherapy (CRT) and adjuvant chemotherapy in patients with locally advanced rectal cancer. The use of oxaliplatin as adjuvant treatment in elderly patients with colon cancer is controversial. We therefore investigated the impact of age on clinical outcome in the CAO/ARO/AIO-04 phase III trial. Patients and methods: We carried out a post hoc analysis of the CAO/ARO/AIO-04 phase III trial evaluating primary and secondary end points according to age. Patient and tumor characteristics, NCI CTC adverse events grades 3–4 (version 3.0), dose intensities as well as survival and recurrence data were analyzed in three specified age groups (<60, 60–70, and ≥70 years). The influence of age as a continuous variable on DFS was modeled using a subpopulation treatment effect pattern plot (STEPP) analysis. Results: A total of 1232 patients were assessable. With the exception of Eastern Cooperative Oncology Group status ( P < 0.001), no differences in patient and tumor characteristics were noticed between age groups. Likewise, toxicity pattern, dose intensities of CRT and surgical results were similar in all age groups. After a median follow-up of 50 months, in patients aged <60 years a significant benefit of adding oxaliplatin to 5-FU-based CRT and adjuvant chemotherapy was observed for local ( P = 0.013) and systemic recurrences ( P = 0.023), DFS ( P = 0.011), and even overall survival (OS; P = 0.044). The STEPP analysis revealed improved hazard ratios for DFS in patients aged 40–70 years compared with elderly patients treated with oxaliplatin. Conclusion: The addition of oxaliplatin significantly improved DFS and OS in younger patients aged <60 years with advanced rectal cancer. Patients aged ≥70 years had no benefit. Clinical Trials Number: NCT00349076